PSYCHOLOGICAL FACTORS TOWARDS SPEAKING ABILITY AT THE FIRST SEMESTER OF ENGLISH DEPARTMENT STUDENTS IN UNDIKMA - Jupri, Jupri; Jumadil, Jumadil (LPPM Institut Pendidikan Nusantara Global, 2023)
This study was meant to analyze the psychological factors that influence the speaking ability of first semester students of English Department students in UNDIKMA, Mataram, West Nusa Tenggara Province. Psychology is the study of the nature of the human soul as well as its process. Psychology deals with the study of external behavior using objective observation methods for stimulation. In addition, there are some psychological factors that hinder students from speaking in English classes such as fear of making mistakes, shyness, anxiety, lack of confidence and lack of motivation. Those factors were commonly caused by their fear of being laughed at by their friends. Some psychological factors such as shyness and anxiety are considered as the main causes of students' reluctance to speak. This study was conducted in a qualitative approach. The population of this research was taken from A and B Classes from the first semester students of English Department students in UNDIKMA, Mataram, West Nusa Tenggara Province. The sample of the study consisted of 30 students. The researchers determined some techniques as the data sources, namely observation, documentation, field notes and tests or interviews. The researchers found that the psychological factors that contribute toward students' speaking abilities are as follows: students who have a fear of making mistakes, shame, anxiety, have low self-confidence, and those have low motivation will make them reluctant to speak in English because they found difficulties in speaking English.